The malignant melanoma diagnosis - Montero, Eustaquio D (Cirugía del Uruguay, 1974)
A revision is made of diagnosis procedures of malignant melanoma, emphasizing the high percentage of errors. Biopsy is always necessary before deciding the therapy to be followed, and mention is made of typical cases where exeresis had to be performed immediately. Problems in making an histological diagnosis are emphasized.